2018
DOI: 10.1038/s41598-018-23840-2
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin interacts directly with the Cysteine 259 residue of STAT3 and induces apoptosis in H-Ras transformed human mammary epithelial cells

Abstract: Signal transducer and activator of transcription 3 (STAT3) is a transcription factor that is latent but constitutively activated in many types of cancers. It is well known that STAT3 plays a key role in inflammation-associated tumorigenesis. Curcumin is an anti-inflammatory natural compound isolated from the turmeric (Curcuma longa L., Zingiberaceae) that has been extensively used in a traditional medicine over the centuries. In the present study, we have found that curcumin inhibits STAT3 signaling that is pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 34 publications
(44 reference statements)
1
46
0
Order By: Relevance
“…Napabucasin has been demonstrated to sensitize tumor cells to checkpoint inhibition and it has been linked to high tumor infiltration of CD8 + T cells in mice bearing 4T1 mammary tumors [217], with similar results being reported in mesothelioma [218]. Notably, curcumin has demonstrated potent anti-STAT3 activity through STAT3 cysteine modification that prevents phosphorylation and it has been found to inhibit proliferation breast cancer [219] and esophageal squamous cell carcinoma [220], with the latter being associated with significant decreases in IL-6. However, while numerous studies using mice models have reported increases in TME infiltration by T cells, suppression of Tregs and MDSCs, and decreased NFκB signaling [221] in tumor bearing animals, curcumin has also been linked to the inhibition of DC activation [222,223].…”
Section: Therapeutic Modulation Of Statsmentioning
confidence: 77%
“…Napabucasin has been demonstrated to sensitize tumor cells to checkpoint inhibition and it has been linked to high tumor infiltration of CD8 + T cells in mice bearing 4T1 mammary tumors [217], with similar results being reported in mesothelioma [218]. Notably, curcumin has demonstrated potent anti-STAT3 activity through STAT3 cysteine modification that prevents phosphorylation and it has been found to inhibit proliferation breast cancer [219] and esophageal squamous cell carcinoma [220], with the latter being associated with significant decreases in IL-6. However, while numerous studies using mice models have reported increases in TME infiltration by T cells, suppression of Tregs and MDSCs, and decreased NFκB signaling [221] in tumor bearing animals, curcumin has also been linked to the inhibition of DC activation [222,223].…”
Section: Therapeutic Modulation Of Statsmentioning
confidence: 77%
“…As already stated in the Introduction, PHGDH was shown as curcumin's target in Angelo's study [19]. Curcumin was also shown to directly interact with the Cysteine 259 residue of STAT3 and induce apoptosis in H-Ras transformed human mammary epithelial cells [21]. Other than these studies, there is no data with respect to curcumin's action on these biomolecules at the level of their mRNA and corresponding protein.…”
Section: Discussionmentioning
confidence: 99%
“…Pleiotropic, beneficial effects of curcumin are attributed to its various modes of action which affect numerous molecules and signaling pathways. Its direct binding to cysteine residues of various proteins, including metabolic enzymes (such as PHGDH and SHMT2) and STAT3, may be very important for alleviating the Warburg effect [18][19][20][21]. Siddiqui et al have recently reported that curcumin downregulates PKM2 expression in cancer cells, consequently decreasing the Warburg effect.…”
Section: Introductionmentioning
confidence: 99%
“…STAT3 represents a promising molecular target for anticancer therapeutics, and there is an immense need to design and develop a novel STAT3 inhibitor which is safe and potent. Several naturally occurring compounds have anti-STAT3 activity, such as curcumin, capsaicin, and guggulsterone (Bhutani et al, 2007;Hahn et al, 2018;Kim et al, 2008). However, most of these inhibitors show modest potency and low selectivity, and this is why the majority of STAT3 inhibitors are difficult to rule out off-target effects and pinpoint (Schust, Sperl, Hollis, Mayer, & Berg, 2006;Song, Wang, Wang, & Lin, 2005).…”
Section: Discussionmentioning
confidence: 99%